Pro Java EE Spring Patterns : best practices and design strategies implementing Java EE patterns with spring framework - Kayal, Dhrubojyoti (Expert's voice in open source., 2008)
The Java landscape is littered with libraries, tools, and specifications. What s been lacking is the expertise to fuse them into solutions to real world problems. These patterns are the intellectual mortar for J2EE software construction. John Vlissides, coauthor of Design Patterns: Elements of Reusable Object Oriented Software Pro Java EE Spring Patterns focuses on enterprise patterns, best practices, design strategies, and proven solutions using key Java EE technologies including JSP, servlets, EJB, and JMS APIs. This Java EE patterns resource, catalog, and guide, with its patterns and nume.